(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Samples of two yams species (Dioscore aalata variety ‘’Azaguié’’ and Dioscorea cayenensis-rotundata variety’’Tambi’’) tubers were subjected to different boiling times after post-harvest storage. These yams tubers species were kept for six (6) months after harvest in an aired storage (26.56 ± 3 ºC; 82 ± 5 % RH). Some biochemical parameters such as dry matter, crude protein, crude fat, total sugars and reducing sugars, starch and cellulose were analyzed using standard procedures and methods. Dry matters, reducing sugars and total sugars contents increased significantly (p ≤ 0.05) during preservation from the month 0 to the month 6 at different boiling times and varied from a tuber to another one. Starch content and cellulose content decreased and increased respectively with increased boiling time during preservation from the month 0 to the month 6.